2005
DOI: 10.1098/rsif.2005.0062
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and differences between induced organ regeneration in adults and early foetal regeneration

Abstract: At least three organs (skin, peripheral nerves and the conjunctiva) have been induced to regenerate partially in adults following application of porous, degradable scaffolds with highly specific structure (templates). Templates blocked contraction and scar formation by inducing a reduction in the density of contractile fibroblasts (probably myofibroblasts) and by preventing these cells to organize themselves appropriately in the wound. In contrast, during early foetal healing, myofibroblasts were absent and wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 95 publications
(117 reference statements)
2
61
1
1
Order By: Relevance
“…It also entraps the hematoma and might prevent the contraction of the fibrinous blood clot, which is a necessary condition for the early phase of regeneration. (58) A structured fibrous tissue (light blue) around the scaffold bridging the defect is observed after 3 months. An onset of mineralized tissue (yellow) around the scaffold and in the endosteal cavity on the proximal end can also be seen, although the morphology is different from that found in an empty scaffold.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also entraps the hematoma and might prevent the contraction of the fibrinous blood clot, which is a necessary condition for the early phase of regeneration. (58) A structured fibrous tissue (light blue) around the scaffold bridging the defect is observed after 3 months. An onset of mineralized tissue (yellow) around the scaffold and in the endosteal cavity on the proximal end can also be seen, although the morphology is different from that found in an empty scaffold.…”
Section: Resultsmentioning
confidence: 99%
“…(60) It also matches Yannas' proposed mechanism of scaffold-guided organ regeneration. (58) He proposed that a scaffold can inhibit contraction, leading to wound closure, which is a necessary condition for the early phase of regeneration. Fibroblasts bind to the scaffold surface and deposit collagen fibers with an orientation parallel to the major cell axis.…”
Section: Discussionmentioning
confidence: 99%
“…Acellular dermal substitutes based on allogeneic, xenogeneic, or synthetic materials [12] are commercial alternatives. Nevertheless, it has been reported that contraction and scar formation cannot be completely prevented by an acellular dermal matrix unless the dermal and epidermal cells have been added [13]. In order to avoid those problems, many composite skin substitutes generated by tissue engineering were developed [12].…”
Section: Introductionmentioning
confidence: 99%
“…Myofibroblast differentiation is regulated by at least TGF-b1, the presence of mechanical tension and an ECM component. A possible mechanism for contraction blocking by a scaffold is as below (Yannas 2005). Once having migrated inside the scaffold and become bound on the extensive surface of the highly porous scaffold, the long axes of myofibroblast lose their in-place orientation, becoming almost randomly oriented.…”
Section: Skinmentioning
confidence: 99%